“… the thought that I could flip and die today made me feel anxious”: A Study of the Experienced Emotions of Novice White-water Kayakers - Schmidt, SK; Barker, Matt; Byrne, J (Cappelen Damm AS - Cappelen Damm Akademisk, 2022)
Learning to white-water kayak often takes place in a stressful environment. This challenges participants’ experiences of the activity, causes emotional responses, and can affect their learning. The purpose of this study is to explore participants’ experienced emotions during an educational white-water kayaking programme. Fifty-eight outdoor students from New Zealand participated. The participants responded to a bespoke questionnaire exploring fleeting somatic arousal and emotion on five different occasions during a kayaking day. Participants’ emotions changed during the activity. Excitement was significantly higher than anxiety across the day. Anxiety was highest before starting the activity. No significant difference was found between the male and female participants’ emotions. A thematic analysis resulted in five themes describing the participants’ emotional experiences. Findings are discussed and related to theory and previous research. These findings present new insights regarding in-the-moment emotional perspectives during a white-water kayaking course for novices.
Keywords: White-water kayaking; Anxiety; Learning; Adventure activities; Gender perspective